The Collaborative Inquiry Model Assisted by the Mathway Application to Improve Students’ Critical Thinking and Collaboration Skills - Aryani, Wayan; I Made Tegeh; Ni Nyoman Parwati (Jurnal Media dan Teknologi Pendidikan, 2025)
Critical thinking and collaboration skills are essential competencies that must be fostered to address the challenges of the Society 5.0 era. However, international assessments such as PISA and TIMSS indicate that students’ mastery of these skills remains relatively low. This study aims to analyze the effect of the Collaborative Inquiry model assisted by the Mathway application on students’ critical thinking and collaboration skills in mathematics learning. The research employed a quasi-experimental design with a non-equivalent pretest–posttest control group design. The population consisted of 11 classes (447 students), with a sample of 120 students from three classes selected through group random sampling. Critical thinking skills were measured using essay tests, while collaboration skills were assessed through a questionnaire. Data were analyzed using Multivariate Analysis of Covariance (MANCOVA) at a 5% significance level. The findings revealed significant differences in critical thinking and collaboration skills simultaneously among students taught with Collaborative Inquiry assisted by Mathway, Collaborative Inquiry without application support, and direct instruction. The study concludes that the integration of the Mathway-assisted Collaborative Inquiry model effectively enhances students’ critical thinking and collaboration skills. These results imply the importance of integrating digital technology into collaborative learning designs to optimize 21st-century competencies.